Library and information science in developing countries contemporary issues - Tella, A. (Adeyinka) 1972-; Issa, A. O. (Abdulwahaab Olanrewaju) 1967-. (Hershey, PA Information Science Reference, 2012)
The field of library and information science is experiencing significant and continued transformation as a result of advancements in digital technology. Adapting to new technologies is crucial for librarians and other information professionals, but there exists a particularly acute gap in technology adoption among developing countries. Library and Information Science in Developing Countries: Contemporary Issues explores the relationship between global technology development and the impact of new technologies on library practice, library education, and information science. Book chapters and case studies in this work provide insight to and support for practitioners and executives concerned with the management of knowledge, information, and organizational development in different types of work environments and learning communities.--Provided by publisher.
Fostering and developing leadership amongst library staff at the University of Zambia Library / Christine Wamunyima Kanyengo -- Pakistan Library and Information Council : a proposal / Midrar Ullah, Khalid Mahmood -- Modernisation of a traditional library / Mehtab Alam Ansari -- Marketing library and information services for effective utilization of available resources : the 21st century librarians and information professionals : which ways and what works? / Tella, Adeyinka ; Ojo, Rachael -- Strategies for marketing an academic library in an African setting / Sylvia A. Ogola, Japhet Otike -- The significance of marketing in library and information science / Monday Obaidjevwe Ogbomo -- Marketing libraries : adopting marketing strategies in Nigerian libraries / Olamidipupo Solomon -- Libraries and preservation of indigenous knowledge in developing countries : the Nigeria experience / Omopupa, K.T. ; Bashorun, M.T. ; Isah, A -- The school librarian in rural China : a stranger among her people / Peter Warning, James Henri -- The future of readership development : how ICTs have influenced user habits and library acquisitions / Elisam Magara -- Status of information ethics teaching at the School of Information Sciences, Moi University, Kenya / Henry N. Kemoni -- An assessment of the perception of library school students towards librarianship at the University of Ilorin : a pilot study / Abdulwahaab Olanrewaju Issa -- Demystifying digital scholarship / Stephen Mutula -- Establishing the digital library : don't ignore the library standards and don' forget the training needed / Alan Hopkinson -- A review of e-government services in Nigeria / Gbola Olasina -- Digital libraries : their challenges and issues in the perspectives of developing countries like India / N.Swaminathan -- Information flow and democratic governance : an analysis of the African experience / F.A. Aremu, H.T. Saka -- Librarians, records managers, and e-government / Cathrine T. Nengomasha -- Information services provision to person with visual impairment in Nigeria : the salient issues / Niran Adetoro -- Organisation of information and the information retrieval system / Edeama O. Onwuchekwa -- Social media in library and information centers / Ayodele John Alonge -- Bibliometric analysis of DECIDOC journal of library & information technology / S. Thanuskodi -- Cataloguing and classification of library resources in the 21st century / Lydia O. Adedibu, Evelyn O. Akinboro, and Titilola A. Abdul salam.
"Premier reference source"--Cover.
Includes bibliographical references and index.
Keywords: Library science -- Developing countries; Information science -- Developing countries; Libraries -- Developing countries; Library education -- Developing countries